Literasi Manajemen Sumber Daya Manusia sebagai Dasar Pengelolaan SDM yang Efektif Gerakan Pemuda Ansor Kecamatan Pagedangan Kabupaten Tangerang - Hafis Laksmana Nuraldy; Surya Budiman; Lily Setyawati Kristianti (Perhimpunan Sarjana Ekonomi dan Bisnis, 2026)
Human Resource Management (HRM) literacy plays a crucial role in strengthening the capacity of youth organizations to manage their human resources effectively and sustainably. This community service program aims to enhance HRM literacy among members of the Gerakan Pemuda Ansor in Pagedangan District so they can improve organizational performance. The method of implementation was carried out at Balai Desa Cicalengka Pagedangan Tangerang Regency on May 19 2026 involving three lecturers from Universitas Pamulang and 32 participants. The activity was conducted through material presentation practical sessions discussion and question-and-answer sessions following preparation implementation and reporting stages. The results showed increased understanding of HRM concepts improved awareness of effective human resource management and stronger commitment to organizational development among participants. It also indicated that continuous training and mentoring are necessary to support sustainable human resource development within youth organizations and to strengthen leadership capacity and teamwork skills in managing community programs effectively. Recommendations include collaboration between universities and community organizations to expand HRM literacy programs and encourage practical implementation in daily organizational activities for long-term impact on youth empowerment and institutional sustainability in local communities. This program contributes significantly to strengthening community based organizational management capacity in Indonesia in sustainable development efforts.